2020
DOI: 10.21203/rs.3.rs-32143/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic value of a five-lncRNA signature in esophageal squamous cell carcinoma

Abstract: Background: The aim of this study was to identify prognostic long non-coding RNAs (lncRNAs) and develop a multi-lncRNA signature for suvival prediction in esophageal squamous cell carcinoma (ESCC). Methods: The clinical and gene expression data from Gene Expression Omnibus database (GSE53624, n=119) were obtianed as training set. A total of 98 paired ESCC tumor and normal tissues were detected by RNA sequencing and used as test set. Another 84 ESCC tissues were used for real-time quantitative PCR(qRT-PCR) and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…We also compared the prognostic ability of this model with those of having been reported prognostic biomarkers for ESCC. The results demonstrated that the 11-lncRNA signature had a higher fidelity than other signatures (Li et al, 2014;Mao et al, 2018;Zhang L. et al, 2020). The combination of cp-score and clinical characteristics improved the 5-year survival prediction, which could identify patients needing more aggressive treatment and surveillance.…”
Section: Discussionmentioning
confidence: 96%
“…We also compared the prognostic ability of this model with those of having been reported prognostic biomarkers for ESCC. The results demonstrated that the 11-lncRNA signature had a higher fidelity than other signatures (Li et al, 2014;Mao et al, 2018;Zhang L. et al, 2020). The combination of cp-score and clinical characteristics improved the 5-year survival prediction, which could identify patients needing more aggressive treatment and surveillance.…”
Section: Discussionmentioning
confidence: 96%